A apropriação dos pátios escolares e a importância no cotidiano de seus usuários - Pacheco, Juliana Arrua (2023)
This master's dissertation proposed to follow a path that involved several areas of knowledge, such as Architecture, Environmental Psychology and Health. The research object of study is the schoolyard, an important space for the child's socialization, a place for exchanges, conviviality, explorations and experiments, a subsystem of open spaces for daily and collective use. This work consists of an analysis of the appropriation of schoolyards by students, considering the return of faceto-face school activities in the context of Covid-19. The research has an approach in the study of the person-environment relationship, considering the theoretical contribution of environmental psychology, and adopts a mixed methods design, such as an exploratory visit, systematic observation, behavioral map, structured and semistructured interview. Based on these methods, was it possible to characterize the courtyards and their users? The research was carried out in three private primary and secondary schools in the municipality of Santa Maria, all with patios that are very heterogeneous among themselves, verifying the form of appropriation of these spaces through the analysis of the user's behavior in relation to the environment. To carry out the evaluation, the work was divided into three stages, where the first consists of the development of the theoretical framework on environmental psychology and the schoolyard, the second stage seeks to gather information for field research and the third is the analysis of data from previous stages. . The sample definition was defined by the difficulty of finding public schools with playgrounds in the courtyards, due to the Covid-19 pandemic. The result of the applied methods and techniques made it possible to understand the needs of its users and to understand the process of appropriation and non-appropriation of school yards in different situations. Through this knowledge, recommendations were proposed in order to achieve an improvement and greater appropriation of the place and to make it more suitable for the students.